Aging, Resilience, and Migration in the Sudano-Sahelian Ecological Belt in Nigeria - Makanju, Adebayo O.M.; Uriri, Alex E. (African Human Mobility Review, 2021)
From the Sudano-Sahelian Zone to the coast, Nigeria is experiencing a variety of environmental change impacts, whether resulting from slow-onset changes or sudden shocks. These uptakes in events are significantly influencing migration decisions and livelihood resilience. The Sudano-Sahelian Ecological Zone, where natural resources form the foundation of livelihoods and food security, is a critical part of the environmental non-migration discussion. This study examines the relationship between environmental changes and non-migration outcomes. It also explores the household resilience of older non-migrants in the geographical area. The study utilized the LSMS-ISA datasets 2010-2018 (920 respondents, persons aged >50). The Food and Agriculture Organization (FAO) RIMA-II methodology was adopted and remodeled to measure a household’s migration resilience and the level of relational variation among multi-faceted drivers of migration. The findings revealed that structural factors such as the environment (soil toxicity, average mean temperature and water security), economic drivers, and agricultural practices were observed to harm households’ resilience and trigger more out-migration. On the other hand, drivers such as social and political factors were found to aid environmental non-migration among households. Furthermore, findings from the trend analysis (2010-2018) revealed that the non-migratory resilience of households was low, although it increased significantly during the examined period. Evidently, due to the heightened impact of environmental stressors, agricultural values and practices would continue to threaten food security and poverty levels, leading to increased cases of the “trapped” aging population.